The Development of Russian-Language Schools in Ukraine (Late 30s-40s of the XXth Century) - Shevchenko, Svitlana (Pedagogical Discourse, 2013)
The given article considers organization of Russian schools in teaching children in Ukraine in the late 30ʼs and 40ʼs in the twentieth century on the base of archived documents It is considered that with beginning of collectivization cultural life of national minorities fell into decay except Russian; it is shown that the beginning of 30th was characterized by such phenomenon in the development and functioning of schools of national minorities, as force Russification. It is traced, that Soviet Government tried to create common requirements as to construction of educational process of schools on the whole territory of the USSR and to give the peoples who lived in Ukraine, real possibility to develop national culture and language. It is distinguished, that during realization of governmental politics as to formation of the Russian minorities of special meaning acquired a problem in the system of formation Russian secondary schools, making lifeliving and effective bodies from guidance, organizational and scientifically-methodological providing. It is investigated, that the content of educational programs and plans of Russian schools fully meet the requirements during the given period.